2012
DOI: 10.1093/humrep/des365
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes following robot-assisted myomectomy

Abstract: There was no funding source for this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 43 publications
5
70
1
3
Order By: Relevance
“…Most uterine ruptures after LM occur during the third trimester [7]. The reported rate of uterine rupture that can be attributed to LM is 1% [8]. Hurst et al [9] reviewed 21 different studies involving a total of 626 patients who had pregnancies following LM.…”
Section: Discussionmentioning
confidence: 99%
“…Most uterine ruptures after LM occur during the third trimester [7]. The reported rate of uterine rupture that can be attributed to LM is 1% [8]. Hurst et al [9] reviewed 21 different studies involving a total of 626 patients who had pregnancies following LM.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported a post-RALM cesarean section rate of 95.7% and a wide range of cesarean section rates after laparoscopic myomectomy (23.5% to 82.1%). 25 A recent Cochrane Systematic Review reported no significant difference in the rate of cesarean section after open and laparoscopic myomectomy (OR 0.59, 95% CI 0.13 to 2.72). 24 The considerably lower rate of cesarean section in our patients may have been influenced by the greater interval of time from the procedure and when they began actively attempting to conceive.…”
Section: Discussionmentioning
confidence: 98%
“…20,[22][23] Similarly, the rate of uterine rupture following RALM has been reported anywhere between 0 to 1.1%. 24,25 Since we first began to perform RALM in our institution, we have maintained a database concerning patient outcomes after undergoing this procedure. The objective of this study was to report post-operative fertility rates and pregnancy outcomes of a large series of patients who had a RALM with a single surgeon at Mount Sinai Hospital from June 2006 to May 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its simplified suturing method, and the possibility of uterine reconstruction, robotic surgery yields similar results and is associated with similar rupture rates as the open procedure, especially in this setting. In a population of 107 patients, Pitter et al (12) reported 92 births and only one case of uterine rupture. Since these patients are still young, they benefit greatly from the minimally invasive approach in terms of long-term sequela, such as adhesions or weakness of the abdominal wall.…”
Section: Application In Benign Gynecological Diseasesmentioning
confidence: 99%